1992
DOI: 10.1161/01.cir.85.1.281
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of prolonged ventricular fibrillation. Immediate countershock versus high-dose epinephrine and CPR preceding countershock.

Abstract: Background. Early countershock of ventricular fibrillation has been shown to improve immediate and long-term outcome of cardiac arrest. However, a number of investigations in the laboratory and in the clinical population indicate that immediate countershock of prolonged ventricular fibrillation most commonly is followed by asystole or a nonperfusing spontaneous cardiac rhythm, neither of which rarely respond to current therapy. The use of epinephrine in doses greater than those currently recommended has recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(64 citation statements)
references
References 42 publications
3
59
1
1
Order By: Relevance
“…2,20 -23 In addition, there is increasing evidence that after 4 minutes of untreated cardiac arrest, precordial compression may best precede defibrillation. 24 This prompted us to conduct controlled preclinical studies with a focus on the benefits of chest compression and specifically the possibility that interruptions in chest compression may prove detrimental.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,20 -23 In addition, there is increasing evidence that after 4 minutes of untreated cardiac arrest, precordial compression may best precede defibrillation. 24 This prompted us to conduct controlled preclinical studies with a focus on the benefits of chest compression and specifically the possibility that interruptions in chest compression may prove detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Yet, the priority of ventilation over precordial compression was challenged and defined as of questionable benefit in settings of "sudden death" based on both experimental and clinical investigations. 2,20 -23 In addition, there is increasing evidence that after 4 minutes of untreated cardiac arrest, precordial compression may best 24 This prompted us to conduct controlled preclinical studies with a focus on the benefits of chest compression and specifically the possibility that interruptions in chest compression may prove detrimental. Chest compression was introduced to modern medicine in the 19th century but was widely adopted only after 1960.…”
mentioning
confidence: 99%
“…In swine with 8 minutes of untreated VF, CPR for 90 seconds followed by defibrillation shock resulted in physiological benefits and a superior response to initial defibrillation in comparison with immediate defibrillation [14]. In a dog model, a brief CPR before defibrillation improved the resuscitation outcome from prolonged VF [15]. Kolarova et al [16] showed that the rate of restored spontaneous circulation increased in proportion to the duration of CPR before defibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies reported that CPR before defibrillation had various benefits [14][15][16]. In swine with 8 minutes of untreated VF, CPR for 90 seconds followed by defibrillation shock resulted in physiological benefits and a superior response to initial defibrillation in comparison with immediate defibrillation [14].…”
Section: Discussionmentioning
confidence: 99%
“…In animals, outcomes improved for prolonged untreated VF when CPR was initiated before defibrillation compared with immediate defibrillation. 30,31 In some clinical studies, 32,33 survival was improved when CPR was initiated before defibrillation in cases of untreated VF lasting longer than 3 to 5 minutes. Thus, as the duration of cardiac arrest increases, initial chest compressions and oxygen delivery to vital tissues may take priority over defibrillation in some patients, with delay of shock delivery until 1 to 2 minutes of CPR has been completed.…”
Section: Resuscitation Pathophysiologymentioning
confidence: 99%